2016
DOI: 10.1002/chem.201600131
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Boron(III) and Phosphorous(V) Complexes of meso‐Triaryl 25‐Oxasmaragdyrins

Abstract: Two unprecedented mixed B(III) /P(V) complexes of meso-triaryl 25-oxasmaragdyrins were synthesized in appreciable yields under mild reaction conditions. These unusual 25-oxasmaragdyrin complexes containing one or two seven-membered heterocyclic rings comprised of five different atoms (B, C, N, O, and P) were prepared by reacting B(OH)(Ph)-smaragdyrin and B(OH)2 -smaragdyrin complexes, respectively, with POCl3 in toluene at reflux temperature. The products were characterized by HRMS and 1D- and 2D-NMR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although 25-oxasmaragdyrin is a good macrocyclic ligand, most of the metal and nonmetal complexes described above clearly indicate that only nitrogen atoms of the dipyrromethene moiety of smaragdyrin are involved in coordination, whereas the other two donor nitrogen atoms, as well as the furan oxygen of the tripyrromethene moiety, remain uncoordinated. We made several attempts to involve the donor atoms of the tripyrrane moiety of 25-oxasmaragdyrin in coordination with metal/nonmetal atoms, and we succeeded in preparing the first examples of mixed B­(III)/P­(V) complexes of meso -triaryl 25-oxasmaragdyrins , containing one or two seven-membered heterocycles that are composed of five different atoms such as B, C, N, O, and P inside the macrocycle. The mixed B­(III)/P­(V) complexes of 25-oxasmaragdyrins 319 and 320 containing one and two seven-membered heterocycles were synthesized by reacting B­(OH)­(Ph)–smaragdyrin 318 and B­(OH) 2 –smaragdyrin 287 , respectively, with POCl 3 in toluene at refluxing temperature (Scheme ).…”
Section: Smaragdyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 25-oxasmaragdyrin is a good macrocyclic ligand, most of the metal and nonmetal complexes described above clearly indicate that only nitrogen atoms of the dipyrromethene moiety of smaragdyrin are involved in coordination, whereas the other two donor nitrogen atoms, as well as the furan oxygen of the tripyrromethene moiety, remain uncoordinated. We made several attempts to involve the donor atoms of the tripyrrane moiety of 25-oxasmaragdyrin in coordination with metal/nonmetal atoms, and we succeeded in preparing the first examples of mixed B­(III)/P­(V) complexes of meso -triaryl 25-oxasmaragdyrins , containing one or two seven-membered heterocycles that are composed of five different atoms such as B, C, N, O, and P inside the macrocycle. The mixed B­(III)/P­(V) complexes of 25-oxasmaragdyrins 319 and 320 containing one and two seven-membered heterocycles were synthesized by reacting B­(OH)­(Ph)–smaragdyrin 318 and B­(OH) 2 –smaragdyrin 287 , respectively, with POCl 3 in toluene at refluxing temperature (Scheme ).…”
Section: Smaragdyrinsmentioning
confidence: 99%
“…Overall, the P­(V) ion in compound 319 was also tetracoordinated and was positioned at 1.64 Å above the mean plane bearing two chloro and oxo as axial groups. The other mixed B­(III)/P­(V) complex of 25-oxasmaragdyrin 320 , which contains two seven-membered heterocycles, has no crystallographic evidence, although the 1D and 2D NMR studies supported the presence of two seven-membered heterocycles inside the smaragdyrin macrocycle and involvement of four pyrrolic nitrogens of the smaragdyrin macrocycle in coordinating with B­(III)/P­(V) ions . Furthermore, the structure also revealed that the pyrrole ring bonded to P­(V) ion was more deviated compared to other heterocyclic rings in the smaragdyrin macrocycle.…”
Section: Smaragdyrinsmentioning
confidence: 99%
“…The emission peaks of SM09 and SM-OR derivatives in tetrahydrofuran were observed at 701 and 704 nm, respectively. A bathochromic shift has been correlated with a higher intramolecular charge-transport ability in the literature. , …”
Section: Resultsmentioning
confidence: 93%
“…A bathochromic shift has been correlated with a higher intramolecular charge-transport ability in the literature. 32,33 The solid-state absorption spectra of studied compounds as thin films coated on FTO substrates were also collected in the reflectance mode. The absorption spectra of all the solid films showed broadened Soret and Q bands compared to those of the corresponding solution spectra in THF.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Chandrashekar and co-workers reported the synthesis of the first stable 25-oxasmaragdyrin and stable Ni­(II) and Rh­(I) complexes of 25-oxasmaragdyrin . More recently, Ravikanth and co-workers reported the synthesis, reactivity, and electronic properties of BF 2 ,, B­(OR) 2 ,, PO 2 ,, and mixed B­(III)/P­(V) complexes of 25-oxasmaragdyrin. However, the preparation of stable azasmaragdyrin has remained elusive, and this has prevented its potential application as a ligand to form metal complexes.…”
Section: Introductionmentioning
confidence: 99%